Treosulfan based reduced toxicity conditioning followed by allogeneic stem cell transplantation in patients with myelofibrosis. Issue 3 (3rd December 2014) - Claudiani, Simone; Marktel, Sarah; Piemontese, Simona; Assanelli, Andrea; Lupo‐Stanghellini, Maria Teresa; Carrabba, Matteo; Guggiari, Elena; Giglio, Fabio; De Freitas, Tiago; Marcatti, Magda; Bernardi, Massimo; Corti, Consuelo; et al.
Abstract: Allogeneic transplantation is the only potentially curative strategy for myelofibrosis, even in the era of new drugs that so far only mitigate symptoms. The choice to proceed to allogeneic transplantation is based on several variables including age, disease phase, degree of splenomegaly, donor availability, comorbidities and iron overload. These factors, along with conditioning regimen and time to transplantation, may influence the outcome of ASCT. We report 14 patients affected by myelofibrosis with a median age of 57 years (range, 41–76) receiving a treosulfan‐fludarabine based reduced toxicity conditioning. Patients (pts) received a stem cell transplantation from an HLA identical ( n = 10) or matched unrelated donor ( n = 4). All pts had a complete myeloablation followed by engraftment and in 12 out of 13 evaluated pts donor chimerism was 100% at 1 month. In most cases a reduction of splenomegaly and a reduction (or resolution) of bone marrow fibrosis was observed. After a median follow‐up of 39 months (range, 3–106), the 3‐year probability of overall survival and disease free survival was 54 +/− 14% and 46 +/− 14%, respectively. The cumulative incidence of non‐relapse mortality at 2 years was 39 +/− 15%. Causes of non‐relapse mortality were: infection ( n = 2), GvHD ( n = 2) and haemorrhage ( n = 1). We can conclude that a treosulfan and fludarabine based conditioning has a potent myeloablative and anti‐disease activity although non‐relapse mortality remains high in this challenging clinical setting. Copyright © 2014 John Wiley & Sons, Ltd.